The Effect of Operating Income and Operating Costs on Net Income - Ananda, Febryandhie; Fajriansyah, Fajriansyah; Annisa, Annisa; Novita, Nova; Kusuma Dewi, Mike (Jurnal Ilmu Manajemen dan Ekonomika, 2024)
This study aims to determine the effect of operating income and operating costs on net profit at PT Gudang Garam Indonesia Tbk. The type of research used is quantitative research. The data sources in this study are literature studies in related journals and books. The sample of this study was 32 quarterly financial reports from 2016 to 2023. The data analysis techniques used were descriptive static tests, classical assumption tests, multiple linear regression, multiple correlation coefficients, adjusted R2 determination tests, and t-tests. This research was conducted at PT Gudang Garam Tbk. Based on the proposed hypothesis, the results of the study indicate that operating income has a negative and significant effect on net profit, while operating costs have a positive and significant effect on net profit, it means operating income don’t have any contribution for gaining income.